PROCESS OF DOUBLE EXTRUDER PROCESS TO INTRINSIC VISCOSITY OF SARGASSUM CRISTAEFOLIUM ALGINATE - Doni Ferdiansyah; Abdul Qadir Jailani (Journal of Aquaculture Development and Environment, 2019)
The purpose of this study was to determine the conditions of the extrusion process which gave a maximum value of intrinsic viscosity response. The 2k factorial design was used to determine the effect of temperature, screw speed and pH on intrinsic viscosity and determine the accuracy of the first-order polynomial model. The temperature treatment, screw speed and pH of alginate extraction extrusion process have a significant influence on intrinsic viscosity. The maximum intrinsic alginate viscosity value of 416.16 ml/g occured under conditions of extrusion process temperature of 60oC, screw speed 75 rpm and pH 10. Quadratic first-order polynomial model, planning of research center temperature 60oC, screw speed of 75 rpm and pH 10 were appropriate.